Free-troposphere ozone and carbon monoxide over the North Atlantic for 2001-2011 - Kumar, Aditya; Wu, S.; Weise, M. F.; Honrath, R.; Owen, R. C.; Helmig, D.; Kramer, L.; Val Martin, M.; Li, Q. (Digital Commons @ Michigan Tech, 2013)
In situ measurements of carbon monoxide (CO) and ozone (O3) at the Pico Mountain Observatory (PMO) located in the Azores, Portugal, are analyzed together with results from an atmospheric chemical transport model (GEOS-Chem) and satellite remote sensing data (AIRS (Atmospheric Infrared Sounder) for CO, and TES (Tropospheric Emission Spectrometer) for O3) to examine the evolution of free-troposphere CO and O3 over the North Atlantic for 2001-2011. GEOS-Chem captured the seasonal cycles for CO and O3 well but significantly underestimated the mixing ratios of CO, particularly in spring. Statistically significant (using a significance level of 0.05) decreasing trends were found for both CO and O3 based on harmonic regression analysis of the measurement data. The best estimates of the possible trends for CO and O3 measurements are -0.31 ± 0.30 (2-σ) ppbv yr-1 and -0.21 ± 0.11 (2-σ) ppbv yr-1, respectively. Similar decreasing trends for both species were obtained with GEOS-Chem simulation results. The most important factor contributing to the decreases in CO and O3 at PMO over the past decade is the decline in anthropogenic emissions from North America, which more than compensate for the impacts from increasing Asian emissions. It is likely that climate change in the past decade has also affected the intercontinental transport of O3.